1983
DOI: 10.1115/1.3167107
|View full text |Cite
|
Sign up to set email alerts
|

Forced Nonlinear Oscillations of an Autoparametric System—Part 2: Chaotic Responses

Abstract: Chaotic oscillations arising in forced oscillations of a two degree-of-freedom autoparametric system are studied. Statistical analysis of the numerically integrated nonperiodic responses is shown to be a meaningful description of the mean square values and the frequency contents of the responses. Some qualitative experimental results are presented to substantiate the necessity of performing the statistical analysis of the responses even though the system and the input are deterministic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…Miles [10] showed that these amplitude and phase modulated motions can themselves bifurcate to chaotic amplitude modulations. No such complex solutions of the amplitude or the averaged equations were found for the subharmonic resonance case investigated by Hatwal et al [6,7].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Miles [10] showed that these amplitude and phase modulated motions can themselves bifurcate to chaotic amplitude modulations. No such complex solutions of the amplitude or the averaged equations were found for the subharmonic resonance case investigated by Hatwal et al [6,7].…”
Section: Introductionmentioning
confidence: 94%
“…The autoparametric system for the present study is shown in Figure 1, and its nondimensional equations of motion are given as follows [6,7]: …”
Section: System Description and Equations Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen from [10,14], the values of ζ 1 , ζ 2 , , 0 are considered to be sufficiently small. Therefore, we introduce a small parameter ϵ(0 < ≪ 1) and make transform , , , , , ,…”
Section: Introductionmentioning
confidence: 99%
“…The early results of system (1.1) with 0 0  F were traced to [10,14] by Hatwal, Mallik and Ghosh based on the harmonic balance method and direct numerical integration. At moderately higher levels of excitations, they observed that over some forcing frequencies and amplitudes, the system response was amplitude and phase modulated harmonic motion, and for even higher excitation levels, the response was found to be chaotic.…”
Section: Introductionmentioning
confidence: 99%